СУДЕБНО-МЕДИЦИНСКАЯ ОЦЕНКА АЛКОГОЛЬНОЙ ИНТОКСИКАЦИИ ПРИ СКОРОПОСТИЖНОЙ СМЕРТИ - Дальжанов, Б.М.; Султанов, М.К.; Еримбетова, З.Б.; Бекжанова, Г.С. (SCIENCE and SOCIETY, 2016)
Having analyzed the results of 238 cases of sudden death, among them the cause of death from intoxication of varying severity has been set, but most cases of sudden death were observed during alcohol intoxication of mild and moderate severity.
Keywords: forensic-medical examination; ethanol; alcohol; alcohol intoxication; poisoning; sudden death